Use of beluntas, vitamin C and E as an antioxidant for reducing off-odor of Alabio and Cihateup duck meat - Rukmiasih .; P.S. Hardjosworo; P.P. Ketaren; P.R. Matitaputty (Indonesian Center for Animal Research and Development (ICARD), 2011)
Besides chewy, red in color, duck meat also have a distorted smell (fishy/off-odor). For consumers who are not familiar, the smell is not preferred. Duck meat contains high unsaturated fatty acids. Unsaturated fatty acid is an ingredient which is prone to oxidation. Two strains: Alabio and Cihateup ducks were used in this study, each consist of 3 replications. Four treatments were: 1. Commercial diet without antioxidant (control = K0); 2. Beluntas leaf meal (0.5%) + commercial diet (KB) 3. Beluntas leaf meal (0.5%) + commercial diet + Vitamin C 250 mg / kg (KBC), 4. Beluntas leaf meal (0.5%) + commercial diet + vitamin E 400 IU/kg (KBE). This experiment was designed in Completely Randomized Design. The result showed that response of Alabio and Cihateup duck to feed treatment in saturated fatty acid content and unsaturated fatty acids in meat and skin of the same, namely the feed treatment of KBE high and low of KBC. Beluntas leaf meal as much as 0.5% + vitamin E in the feed could be reduced the intensity of off-odor and maintain good performance of duck. Key Words: Alabio Duck, Cihateup Duck, Beluntas Leaf Mael, Vitamint C, Vitamint E